(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Lecturing in higher institutes of learning is a profession that is defined by intellectual labour and academicians are required to apply knowledge from multiple domains. As knowledge workers academic staff can benefit from collaboration among themselves and sharing of their professional experience. The aim of this study is to develop a prototype Knowledge Management System (KMS) to assist academic staff to network, learn and share of knowledge and resources in Libya Institutes of Higher Learning. The methodology used in this research is Design Based Research (DBR). Six academicians from Libya Institutes oof Higher Learningwere interviewed to determine the system requirements. The prototype was modelled using UML and developed using HTML5 and CSS web development technologies. To evaluate the system, survey instruments were designed and administered based on Technology Acceptance Model (TAM) 2, ease of use constructs and the academicians’ specifications. Fifty academicians were approached to evaluate the prototype after using the system. 96% of the academicians who evaluated the prototype, rated it as easy to use. 84% of the respondents said Yes, they will use it if it is fully implemented. 90% indicated that they will recommend it to their friends. This research findings contribute to the body of knowledge related to Knowledge Management System by applying Design Based Research methodology to develop an artefact and utilized TAM as theory in designing, developing and evaluating the prototype. The artefact from this study is an innovation that would be useful to academicians to connect, collaborate and share knowledge and resources. It also provides opportunity for researchers to develop applications for networking, collaboration and sharing of knowledge and learning